2011
DOI: 10.1681/asn.2011010006
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Immunosuppressive Regimens in Renal Transplantation

Abstract: The optimal long-term regimen for immunosuppression for kidney transplant recipients is unknown. We conducted a randomized trial involving 150 kidney transplant recipients to compare tacrolimus/sirolimus, tacrolimus/mycophenolate mofetil (MMF), and cyclosporine/sirolimus. All patients received daclizumab induction and maintenance corticosteroids. Median follow-up was 8 yr post-transplant. Acute rejection (AR) occurred significantly less often among those treated with tacrolimus/MMF (12%) than among those treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 28 publications
3
71
0
Order By: Relevance
“…This is similar to findings in some other studies, a few of which had similar methodology to ours. [6,13] Several further studies, however, report a significantly greater role for tacrolimus in the causation of NODAT. [9,12] Our finding may reflect the relatively small number of patients who received tacrolimus compared with cyclosporine in our cohort.…”
Section: Researchmentioning
confidence: 99%
“…This is similar to findings in some other studies, a few of which had similar methodology to ours. [6,13] Several further studies, however, report a significantly greater role for tacrolimus in the causation of NODAT. [9,12] Our finding may reflect the relatively small number of patients who received tacrolimus compared with cyclosporine in our cohort.…”
Section: Researchmentioning
confidence: 99%
“…57 A randomized control trial by Guerra and associates suggested maintenance therapy with tacrolimus-MMF was more favorable than either tacrolimus-sirolimus or cyclosporinesirolimus. 58 To address the question regarding whether nephrotoxicity is an issue with tacrolimus, Ekberg and associates pooled data from 3 large randomized de novo RT studies (Symphony, Fixed-Dose concentration controlled, and OptiCept) and explored the relations of renal function at 1 year after RT (estimated GFR) with tacrolimus levels and MMF dose measured over the previous 6 months. Lower tacrolimus levels and higher MMF doses were associated with significantly better renal function.…”
Section: Rescue Therapymentioning
confidence: 99%
“…Therefore, concentration monitoring has been needed to prevent rejection and toxicity risk. Limited studies have been done so far to assess the transplant outcomes with an mTOR inhibitor-based initial regimen with CNI minimization, with the notable ones being the ASSET study (2012) [22][23][24][25][26][27][28][29] In 2012, Langer and associates in their ASSET study compared de novo introduction of very-lowdose tacrolimus (1.5-3 ng/mL) and everolimus (3-8 ng/mL) with low-dose tacrolimus (1.5-3 ng/mL) and everolimus (3-8 ng/mL). These have been used in a combination with oral steroids following basiliximab induction in renal transplant patients.…”
Section: Mammalian Target Of Rapamycin-based Initial Regimen With Lowmentioning
confidence: 99%